Short Communication: Genetic variability, heritability, correlation, and path analysis in tomato (Solanum lycopersicum) under shading condition - ARYA WIDURA RITONGA; M. ACHMAD CHOZIN; MUHAMAD SYUKUR; AWANG MAHARIJAYA; SOBIR SOBIR (Society for Indonesian Biodiversity, 2018)
Authors. 2018. Genetic variability, heritability, correlation, and path analysis in tomato (Solanum lycopersicum) under shading condition. Biodiversitas 19: 1527-1531. Information on genetic variability, heritability and character association between quantitative characters with yield are crucial in crop improvement. Eighteen genotypes of tomato were evaluated to study the quantitative genetic of yield and various yield attributing character under shading condition at Pasir Kuda Station, Bogor Agriculture University, West Java, Indonesia from August 2016 until January 2017. The result showed that plant height, dichotomous height, fruit weight, fruit length, fruit diameter, number of fruit per plant, and the fruit set had broad genetic variability and high heritability. Characters with broad genetic variability and high heritability can be used as sources in shading tolerance tomato improvement. Fruit weight and fruit number per plant had significant positive correlation coefficient and direct positive effect on fruit yield per plant. It is, therefore, recommended that fruit weight and fruit of number per plant should be given due importance in selection to develop shading tolerance variety in tomato